Goldilocks and the three bears = : Boucle d'or et les trois ours - Lomba, Ana.; Cornejo, Santiago; Wenzel, Dominique (New York : McGraw-Hill, 2006)
Presents a children's book for early readers written in both England and French about Goldilocks and the three bears, and contains a thirty-minute audio CD.
"McGraw-Hill's easy French storybook, the fun way to learn 50 new French words!".
Translation of: Goldilocks and the three bears.
1.4
K-3
Text in English and French.
Keywords: Bears -- Folklore; French language materials -- Bilingual; Bears -- Folklore; Bilingual books -- English-French.